A magneto-electro-optical effect in a plasmonic nanowire material - Valente, João (2018)
Electro- and magneto-optical phenomena play key roles in photonic technology enabling light modulators, optical data storage, sensors and numerous spectroscopic techniques. Optical effects, linear and quadratic in external electric and magnetic field are widely known and comprehensively studied. However, optical phenomena that depend on the simultaneous application of external electric and magnetic fields in conventional media are barely detectable and technologically insignificant. Here we report that a large reciprocal magneto-electro-optical effect can be observed in metamaterials. In an artificial chevron nanowire structure fabricated on an elastic nano-membrane, the Lorentz force drives reversible transmission changes on application of a fraction of a volt when the structure is placed in a fraction-of-tesla magnetic field. We show that magneto-electro-optical modulation can be driven to hundreds of thousands of cycles per second promising applications in magneto-electro-optical modulators and field sensors at nano-tesla levels.